‘The Language of the Future’ and the Crisis of Modernity: Mina Loy’s ‘Aphorisms on Futurism’ - Yasna Bozhkova (Angles)
This paper focuses on Mina Loy’s “Aphorisms on Futurism,” written in Florence while she was involved with Futurist leaders F.T. Marinetti and Giovanni Papini, and first published in 1914 in Alfred Stieglitz’s Camera Work. In Loy’s “Aphorisms” emerges the utopian idea of a poetic “language of the Future,” which reflects the Futurist project to destroy language, replacing a traditional syntax that has become obsolete with a telegraphic language of modernity. On her own copy of “Aphorisms,” Loy later replaced the word “Futurism” with the word “Modernism,” suggesting, perhaps with a certain irony, that the project of a poetic “language of the Future” extends beyond the aesthetics of Italian Futurism to the Modernist movement as a whole, yet pinpointing the problem of Modernism as a chain reaction of “isms,” each with its own agenda of radical experimentation in search of a new poetic language of modernity. Taking this key later revision as its departure point, this paper reads Loy’s text with a double focus: on the one hand, situating it in the context of its composition and reading it through the prism of Futurism’s incendiary rhetoric, and on the other, within a broader definition of Modernism, tracing how this violent call for destruction of traditional discourse later collapses into a poetics of silence, whose dimensions are both aesthetic and historical. The ironic ambivalence of “Aphorisms” is already inherent in its strategic generic ambiguity: it reads both as a Futurist manifesto and as a series of aphorisms, oscillating between the revolutionary rhetoric of the manifesto and the ironic silence of the aphorism, which becomes a key vehicle for reflecting ambivalently on the crisis of modernity. Finally, this paper also suggests that the aesthetic principles outlined in Loy’s “Aphorisms” can be used as an interpretative lens through which to examine her poetic strategies of extreme concision and density.